Headache and pneumatized superior concha - Kaygusuz, I.; Murat, A.; Susaman, N.; Karlidag, T.; Keles, E.; Yalcin, S.; Sakallioglu, O. (Galenos Yayincilik, 2007)
Objectives: The conchal pathologies are the most important part of the rhinological originated headaches. The aim of this study was to investigate the association between headache and pneumatization of superior concha. Methods: 150 patients (113 female, 37 male) with headahce were included to the study. The patients were examined for ear nose throat pathologies and consultated by neurology and ophthalmology. Their both paranasal sinus and brain computerized tomographies (CT) were evaluated. Ninety-six patients who have nasal septal deviation, sinusitis findings, pathologies of procesus uncinatus (sloping to lateral or medial), bulla ethmodalis (prominent to anterior, pneumatized) and middle concha (paradox middle concha, concha bullosa) and hypertrophy of inferior concha, according to paranasal sinus CT and nasal endoscopic examination; 7 patients who have vascular type headache and migraine; 14 patients who have ophthalmic refraction fault, totally 117 patients were excluded to the study. Results: The study was completed with 33 patients (28 female, 5 male). The mean age of the 33 patients was 31.00 +/- 11.00 (ranged from 17 to 50). Headache were localized on frontal region in 28 patients (84.8%, 25 bilateral and 3 unilateral), on occipital region in 3 patients (9.1%) and on vertex in 2 patients (6.1%). The pneumatization of superior concha were observed bilaterally in 8 patients (24.2%) and unilaterally in 3 patients (9.1%). Conclusion: The pneumatization of superior concha should be considered in patients who have headache but no pathologic examination findings. Nasal endoscopic examination and paranasal sinus CT evaluation are required in these patients for mentioned pathology.
Keywords: Concha; headache; concha bullosa